CFD analysis of an exceptional cyclist sprint position - Blocken, B.; van Druenen, T.; Toparlar, Y.; Andrianne, T. (Sports Engineering, 2019)
A few riders have adopted a rather exceptional and more aerodynamic sprint position where the torso is held low and nearly horizontal and close to the handle bar to reduce the frontal area. The question arises how much aerodynamic benefit can be gained by such a position. This paper presents an aerodynamic analysis of both the regular and the low sprint position in comparison to three more common cycling positions. Computational fluid dynamics simulations are performed with the 3D RANS simulations and the transition SST k-? model, validated with wind-tunnel measurements. The results are analyzed in terms of frontal area, drag coefficient, drag area, air speed and static pressure distribution, and static pressure coefficient and skin friction coefficient on the cyclist surfaces. It is shown that the drag area for the low sprint position is 24% lower than for the regular position, which renders the former 15% faster than the latter. This 24% improvement is not only the result of the 19% reduction in frontal area, but also caused by a reduction of 7% in drag coefficient due to the changed body position and the related changes in pressure distribution. Evidently, specific training is required to exert large power in the low sprint position.